If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 = -4(-7 + 1) + 5(8 + 2y) Combine like terms: -7 + 1 = -6 -2 = -4(-6) + 5(8 + 2y) Multiply -4 * -6 -2 = 24 + 5(8 + 2y) -2 = 24 + (8 * 5 + 2y * 5) -2 = 24 + (40 + 10y) Combine like terms: 24 + 40 = 64 -2 = 64 + 10y Solving -2 = 64 + 10y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-10y' to each side of the equation. -2 + -10y = 64 + 10y + -10y Combine like terms: 10y + -10y = 0 -2 + -10y = 64 + 0 -2 + -10y = 64 Add '2' to each side of the equation. -2 + 2 + -10y = 64 + 2 Combine like terms: -2 + 2 = 0 0 + -10y = 64 + 2 -10y = 64 + 2 Combine like terms: 64 + 2 = 66 -10y = 66 Divide each side by '-10'. y = -6.6 Simplifying y = -6.6
| 5-5(a+2)=7+a | | 6z^2+19z+10=0 | | x/(-2)=-61 | | (4x+1)(3x-2)=0 | | 3s-2=5s-6 | | -3r-13r=2 | | 5v^2+15v-50=0 | | 80-x=91 | | 16n+8=49n+67 | | x/(-4)=-34 | | 24*14=x(x+8) | | 24*10=8(8+x) | | 8+x=14+10 | | 8x=10*14 | | -270*x=-30 | | (7+6i)x(3+i)= | | 3(6x+9)-10x=1 | | 4y+2=0 | | 4x^2+8x+6=0 | | 3y-3=7y-1 | | -110+x=19 | | 4.5+3.4= | | 2(x+2)-9=4x-2(5+x) | | 5x=-x+18 | | 5x-(x-4)=24 | | -11(3.2)(.12(-12))= | | (7+6i)(3+i)= | | 2x+19=3x+2 | | 3x-10=-2x+28 | | -12t+20+8t=5t-9 | | (5+x)(4+x)(x+3)=420 | | 27=7+37t-16t^2 |